Global gene expression analyses of the alkamide-producing plant Heliopsis longipes supports a polyketide synthase-mediated biosynthesis pathway - Génesis V. Buitimea-Cantúa; Nayelli Marsch-Martinez; Patricia Ríos-Chavez; Alfonso Méndez-Bravo; Jorge Molina-Torres (PeerJ, 2020)
Background Alkamides are plant-specific bioactive molecules. They are low molecular weight N-substituted α-unsaturated acyl amides that display biological explicit activities in different organisms from bacteria, fungi, insects to mammals and plants. The acyl chain has been proposed to be biosynthesized from a fatty acid; however, this has not been demonstrated yet. Heliopsis longipes (Asteraceae) accumulates in root a C10 alkamide called affinin in its roots, but not in leaves. The closely related species Heliopsis annua does not produce alkamides. To elucidate the biosynthetic pathway of the alkamides acyl chain, a comparative global gene expression analysis contrasting roots and leaves of both species was performed. Methods Transcriptomics analysis allowed to identify genes highly expressed in H. longipes roots, but not in tissues and species that do not accumulate alkamides. The first domain searched was the Ketosynthase (KS) domain. The phylogenetic analysis using sequences of the KS domain of FAS and PKS from different organisms, revealed that KS domains of the differentially expressed transcripts in H. longipes roots and the KS domain found in transcripts of Echinacea purpurea, another alkamides producer species, were grouped together with a high bootstrap value of 100%, sharing great similarity. Among the annotated transcripts, we found some coding for the enzymatic domains KS, AT, ACP, DH, OR and TE, which presented higher expression in H. longipes roots than in leaves. The expression level of these genes was further evaluated by qRT-PCR. All unigenes tested showed higher expression in H. longipes roots than in any the other samples. Based on this and considering that the acyl chain of affinin presents unsaturated bonds at even C numbers, we propose a new putative biosynthesis pathway mediated by a four modules polyketide synthase (PKS). Results The global gene expression analysis led to the selection of a set of candidate genes involved in the biosynthesis of the acyl chain of affinin, suggesting that it may be performed by a non-iterative, partially reductive, four module type I PKS complex (PKS alk) previously thought to be absent from the plant kingdom.